Prior Pronunciation Knowledge Bootstraps Word Learning - Johnson, Khia Anne; Mellesmoen, Gloria Madeleine; Lo, Roger Yu-Hsiang; Gick, Bryan (Frontiers in Communication, 2018)
Learners often struggle with L2 sounds, yet little is known about the role of prior pronunciation knowledge and explicit articulatory training in language acquisition. This study asks if existing pronunciation knowledge can bootstrap word learning, and whether short-term audio-visual articulatory training for tongue position with and without a production component has an effect on lexical retention. Participants were trained and tested on stimuli with perceptually salient segments that are challenging to produce. Results indicate that production knowledge plays an important role in word learning. While much about the extent and shape of this role remains unclear, this study sheds light in three main areas. First, prior pronunciation knowledge leads to increased accuracy in word learning, as all groups trended toward lower accuracy on pseudowords with two novel segments, when compared to those with one or none. Second, all training and control conditions followed similar patterns, with training neither aiding nor inhibiting retention; this is a noteworthy result as previous work has found that the inclusion of production in training leads to decreased performance when testing for retention. Lastly, higher production accuracy during practice led to higher retention after the word-learning task, indicating that individual differences and successful training are potentially important indicators of retention. This study provides support for the claim that pronunciation matters in L2 word learning.